Lexicostatistic of Javanese and Banjarese Languages in Central Kalimantan: A Comparative Linguistic Study - Rifka Hikmahwati; M Markhamah (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the kinship between Javanese and Banjarese spoken in Central Kalimantan using a mixed qualitative and quantitative approach. The quantitative method is applied through lexicostatistical techniques, while the qualitative method focuses on analyzing linguistic similarities between the two languages. The main problem addressed in this study is the limited number of comparative studies that specifically examine the lexical relationship between Javanese and Banjarese. This research contributes by offering a detailed mapping of lexical similarities and sound change patterns, as well as providing recent empirical data from a region that has not been widely studied. The research data consist of 207 basic vocabulary items from the Swadesh list collected through observation and conversational methods. Four informants participated, including two native speakers of Javanese and two native speakers of Banjarese. The analysis was conducted by grouping vocabulary into categories, identifying pairs of words with similar forms and cognates, and describing phonemic correspondence patterns. The results show 44 pairs of related words. Identical pairs are the most frequent, totaling 26 word pairs, while the remaining pairs exhibit sound change patterns. These include phonemic correspondences between /a/ and /e/, /a/ and /o/, /u/ and /o/, the omission of the phoneme /h/, and the change of the phoneme /b/ to /w/. The percentage of relatedness is 21%, placing Javanese and Banjarese in the language stoch category according to Swadesh’s classification. These findings indicate regular and historically explainable phonemic similarities and differences, contributing to the study of language relatedness in Central Kalimantan.